2022
DOI: 10.1016/j.therap.2022.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Does the public know when a scientific controversy is over? Public perceptions of hydroxychloroquine in France between April 2020 and June 2021

Abstract: Objectives In the early stages of the coronavirus disease 2019 (COVID-19) pandemic, chloroquine and its derivatives such as hydroxychloroquine (HCQ) were widely commented upon both within the scientific community and in the media. This paper explores the different factors that influenced public perceptions in France of the efficacy of HCQ as well as their evolution between April 2020 and June 2021. Methods This article draws on 5 surveys conducted among representative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…As expected, with an enormous amount of often changing and not always valid [30] COVID-19-related information being broadcast across all media channels during the study period and specific controversies over treatments (e.g., efficacy of chloroquine [31] ), CovIO was higher than CIO and increased over time in our study (when adjusting for CoVID-19 related variables such as personal infection and preoccupation). While CIO was higher in this sample compared to our previous study in 2016 [10] , it was stable across the two survey waves and this difference may reflect the fact that our previous study recruited a convenience sample of people specifically interested in cancer research and that participants not affected by cancer were found to have higher CIO than cancer patients or caregivers [10] .…”
Section: Discussionsupporting
confidence: 70%
“…As expected, with an enormous amount of often changing and not always valid [30] COVID-19-related information being broadcast across all media channels during the study period and specific controversies over treatments (e.g., efficacy of chloroquine [31] ), CovIO was higher than CIO and increased over time in our study (when adjusting for CoVID-19 related variables such as personal infection and preoccupation). While CIO was higher in this sample compared to our previous study in 2016 [10] , it was stable across the two survey waves and this difference may reflect the fact that our previous study recruited a convenience sample of people specifically interested in cancer research and that participants not affected by cancer were found to have higher CIO than cancer patients or caregivers [10] .…”
Section: Discussionsupporting
confidence: 70%
“…19 Finally, in and around the Marseille metropolis, the image of a rebellious territory was reinforced since the first months of the epidemic in France through the hypermediatized Pr Didier Raoult. Based in Marseille, he was a promoter of a controversial treatment against Covid-19 based on hydroxychloroquine and azithromycin, 20 and later held ambiguous positions regarding Covid-19 vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in and around the Marseille metropolis, the image of a rebellious territory was reinforced since the first months of the epidemic in France through the hypermediatized Pr Didier Raoult. Based in Marseille, he was a promoter of a controversial treatment against Covid-19 based on hydroxychloroquine and azithromycin (Schultz et al 2022), and later held ambiguous positions regarding Covid-19 vaccination. He has become a local icon, thanks to his anti-system positions, and against the hostility of most of the medical world towards his work.…”
Section: Discussionmentioning
confidence: 99%